Study on management of congenital diaphragmatic hernia - Ali, MB; Saha, AK; Hossain, SM; Ahmed, SFU; Maruf, AA (Mediscope, 2016)
Congenital diaphragmatic hernia (CDH) is a defect in the dome of diaphragm, more often in left and posterior-lateral that permits the herniation of abdominal contents into the thorax. Treatment requires stabilization prior to surgical correction. The best hospital series report 80-100% survival. The objective of the study was to present the experience regarding management of selected respiratory stable cases of CDH in non intensive care setup. Retrospective case series analysis was conducted on total 17 stable acyanotic patients with or without oxygen support and left sided defect were planned for surgical correction. Surgery was done per abdominally through left subcostal incision. In postoperative ward, patients received oxygen with nasal cannula and assisted ventilation with artificial manual breathing unit (AMBU) bag through ETT (endotracheal tube) if required. Patients vital parameters; pulse, respiration, oxygenation (SpO2) and hydration were monitored throughout postoperative period. Oral feeding was started after bowel movement on 2nd or 3rd postoperative day. Plain X-ray of the thorax and abdomen was repeated on 4th or 5th postoperative day to asses lung expansion. Postoperative follow up was given at one week and one month after discharge. The age of the patients ranged from 2 days to 2 year 6 months and the mean (SD) age and body weight was 1.2 (0.6) and 5.0 (1.2), respectively. The male/female and vaginal/cesarean delivery ratios were 12:5 and 10:7, respectively. Associated congenital anomalies found were 3 (17.7%): 1 (5.9%) cleft lip and palate, 1 (5.9%) undescended testes and 1 (5.9%) hypospadias. Respiratory distress was found in 15 (88.2%) patients and 2 (11.8%) patients with recurrent abdominal distension and vomiting. One baby needed assisted ventilation with endotracheal tube and AMBU bag for 24 hours postoperatively. One case with pneumothorax required chest drain for 5 days. All other patients had good lung expansion, correction of mediastinal shifting and no evidence of any pleural effusion. All babies tolerated feeding well postoperatively after bowel movement. Survival rate was 100%. The higher survival rate among the more mature babies suggests natural selection of those with minimal respiratory impairment. In our short series survival was 100% where surgical correction was made on selective 17 cases of left sided CDH in a non intensive care setup. Mediscope Vol. 3, No. 1: January 2016, Pages 16-21